2020
DOI: 10.1111/hel.12769
|View full text |Cite
|
Sign up to set email alerts
|

Designing strategies for eradication of Helicobacter pylori based on prevalence patterns of infection and antibiotic resistance in a low‐income, medically underserved community in the United States

Abstract: Background Regional variation in Helicobacter pylori resistance patterns is a significant contributing factor for the ineffectiveness of traditional treatments. To improve treatment outcomes, we sought to create an individualized, susceptibility‐driven therapeutic approach among our patient population, which is one of the poorest in the nation. It is medically underserved, minority‐predominant and has high incidence of H pylori infection. Methods We compiled various factors involved in the antibiotic resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In other words, patients who experience decreased gut microbial diversity as they age, potentially mediated by diet or chronic inflammation, may be more prone to H. pylori infection, particularly by mid-adulthood. In our previous study of 2,014 H pylori patients, we observed that 80% of our patients were above the age of 40 years [23] . Antibiotic exposure is known to alter the gut microbiome, and increased rates of antibiotic resistant- H. pylori among older adults have been attributed to increased antibiotic use compared to younger patients [2, 43, 44] .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In other words, patients who experience decreased gut microbial diversity as they age, potentially mediated by diet or chronic inflammation, may be more prone to H. pylori infection, particularly by mid-adulthood. In our previous study of 2,014 H pylori patients, we observed that 80% of our patients were above the age of 40 years [23] . Antibiotic exposure is known to alter the gut microbiome, and increased rates of antibiotic resistant- H. pylori among older adults have been attributed to increased antibiotic use compared to younger patients [2, 43, 44] .…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, unweighted UniFrac PERMDISP did not reveal differences in dispersion among H. pylori patients versus control subjects ( F = 0.0506, p = 0.809), but weighted UniFrac PERMDISP did ( F = 6.82955, p = 0.017). We also explored the effect of the use of proton pump inhibitors (PPIs) via beta diversity analysis as PPIs are the medications commonly given to H. pylori patients and we had previously noted their influence on the antibiotic resistance of H. pylori [23] . Unweighted UniFrac PERMANOVA identified differences between PPI users and non-users across all participants ( F = 1.939, p = 0.012), though the magnitude of the effect was smaller than that seen for H. pylori infection as described above.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…for any infection decreased the chance of eradication, while past use of PPI, metronidazole and tetracycline increased the chances of eradication. These results suggest that the clinical history may obviate the need for laboratory testing in predicting resistance [24]. Here we review clinical factors associated with antibiotic resistance that may provide avenues for research to predict which patients are at increased risk of treatment failure and subsequently guide the selection of successful and cost-effective personalized empiric therapy.…”
Section: Introductionmentioning
confidence: 99%